Portrayal of Philippine superheroes in film - Secuelan, Irene V.
The research design is descriptive. The researchers identified and explained the existing elements and characteristics of Philippine superhero film and its main superhero characters through content analysis. The researchers used a codebook as their basis for coding. Based on findings, the common elements of a Philippine superhero film are lower-class human identity, family dilemma, hiding of superhero from love interest, man vs. man conflict, superhero and villain fighting in a battle, superhero winning, community values, and comedy. A Philippine superhero is a handsome and muscular male young adult who has enhanced human abilities that were acquired accidentally, puts on a conservative superhero costume, and has same physical attributes and personality with human counterpart. The study concludes that film is a powerful tool for reflecting Philippine society, its history and culture, through signs. A Philippine superhero film depicts reality but through entertainment and comedy to gratify Filipinos